2007
DOI: 10.1292/jvms.69.1033
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Evaluation of Canine Ovarian Cysts

Abstract: ABSTRACT. To clarify the immunohistochemical characteristics of canine ovarian cysts, 109 canine ovarian cysts (57 cysts of subsurface epithelial structures: SES, 26 graafian follicle cysts, 12 cystic rete ovarii and 14 cysts difficult to classify morphologically) were examined regarding their lining cells immunohistochemically using antibodies against placental alkaline phosphatase (PLAP), S100, inhibin α, desmin and AE1/AE3. Both cysts of SES and cystic rete ovarii had a positive immunoreaction to desmin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 12 publications
3
24
0
Order By: Relevance
“…Pursuing research is needed to further characterize cystic structures of the ovaries, which in detail is only possible by histological and immunohistochemical examination (Akihara et al 2007; Ortega-Pacheco et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pursuing research is needed to further characterize cystic structures of the ovaries, which in detail is only possible by histological and immunohistochemical examination (Akihara et al 2007; Ortega-Pacheco et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of ovarian cysts in bitches are either case reports, focusing on one or a few individuals (Shille et al 1984; Ervin and Homans 1986; Arlt et al 2011; Sontas et al 2011), or studies focusing on one attribute of the disease or another (e.g. histology or reproductive pathologies at all) (Trasch et al 2003; Akihara et al 2007; Ortega-Pacheco et al 2007). While these previous studies have provided invaluable information about the nature of the disease in dogs, additional details about the connection between gross pathology and endocrinology of ovarian cysts in dogs are needed for a better understanding of their potential for causing disease.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cysts in women are often associated with reproductive disorders like polycystic ovary syndrome (PCOS) [6]. They have been also reported in many animals, including dogs, cats, cattle, horses, pigs and monkeys [1,11,12]. Among monkeys, ovarian cysts in macaques such as rhesus and cynomolgus monkeys have been well documented in previous reports [3,12].…”
mentioning
confidence: 96%
“…The cells lining cysts also lose their original structure with the expansion of the cysts [1]. Therefore, immunohistochemistry can be useful in differentiating different types of ovarian cysts.…”
mentioning
confidence: 99%
“…However, cystic rete ovarii, which is another cystic lesion of the ovary, is rather rare in animals including the dog, cat, guinea pig and African green monkey [8,9,10, 13]. Moreover, immunohistochemical observations of cystic rete ovarii in animals are very limited, which makes it difficult to determine the origin of the cyst [1]. Recently, the authors have reported a case of cystic rete testis in a male rabbit [6].…”
mentioning
confidence: 99%